ICHTHYOFAUNAL ASSEMBLAGE OF BALANGA DAM GOMBE STATE, NIGERIA - UMAR, ABUBAKAR M.; SULAIMAN, NAZEEF; BELLO, MOHAMMED T. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
The icthyofaunal identification of Balanga Dam has been carried out. Fish samples were collected from the local fishermen in two landing sites. Top and bottom set foul hook lines, gill and cast net of different mesh sizes were used for fish capturing. Fish species were preserved and transported to the laboratory for identification purpose. Different identification keys were used as reference materials during fish identification. The Dam show high ichtyofaunal diversity as its recorded 15 fish species belonging to 11 families. It is reveals that family Mormyridae had highest number of three (3) species, followed by Bagridae and Mochokidae with two (2) species each, while the remaining families had only one (1) species respectively. Research in to fish condition factor and water quality of the dam is needed to ascertain the general fish productivity of the Dam.